Global warming, pollution and cognitive developments The effects of high pollution and temperature levels on cognitive ability throughout the life course - Horvath, Diana (OECD Publishing, 2022)
Global warming and air pollution threaten human health, economic prosperity and human capital accumulation. The current review presents empirical findings on the effect of adverse environmental conditions on cognition, with a focus on pollution and high temperatures. The review takes a life-course perspective and quantifies both the direct and indirect effects of cumulative and transitory exposure to adverse conditions on cognition starting in-utero all the way to exposure in old age. The review makes clear that exposure to pollutants and high temperatures has economically meaningful costs for both individuals and societies, stemming from lower human capital accumulation. Furthermore, the evidence presented indicates that adverse environmental conditions have large distributional consequences, leading to widening disparities in educational opportunities both across countries and across socio-economic groups within-countries. The review discusses the mechanisms underpinning these effects and explores policies that have the potential to mitigate the negative impact of adverse conditions on cognition
Keywords: Social Issues/Migration/Health; Employment; Environment